Osmotic Pressure Induced Morphological Transformation of Membranized Coacervates - Qiao, Xin; Wang, Xiaoliang; Chen, Haixu; Huang, Yan; Li, Shangsong; Li, Luxuan; Huang, Xin (Journal of the American Chemical Society, 2025)
The stimulus-response behavior of protocells under environmental osmotic pressure changes has long been a subject of scientific inquiry. Herein, we demonstrate a way to membranized coacervate microdroplets based on cholesterol anchoring of phospholipids, which provides enhanced stability, enabling morphological transformations instead of dissociation during subsequent osmotic pressure changes. In hypotonic environments, these membranized coacervates equilibrate osmotic pressure through transient internal vacuole formation, concomitant with a transmembrane substrate influx that triggers enzymatic reaction acceleration. By contrast, in a hypertonic environment, the membranized coacervate responds with bursting-like deformation that can then quickly recover due to the anchoring effect of cholesterol on phospholipids. Notably, it is found that such bursting-like deformation could even successfully induce endocytosis of Staphylococcus aureus by the membranized coacervates. Furthermore, through the integration of Coa@DMPC’s osmotic responsiveness, internal actin polymerization activated by the endocytic S. aureus is achieved. Not only our proposed method of phospholipid membranization of the coacervate could contribute a new model to mimic more complex bionic structures, but also the revealed morphological response behavior of the membranized coacervate under various osmotic pressure changes is expected to help explain the stress behaviors and emerging unique properties of cells in similar environments.